Impact of interprofessional collaboration on chronic disease management: Findings from a systematic review of clinical trial and meta-analysis. Issue 2 (February 2021) - Pascucci, Domenico; Sassano, Michele; Nurchis, Mario Cesare; Cicconi, Michela; Acampora, Anna; Park, Daejun; Morano, Carmen; Damiani, Gianfranco
Highlights: Interprofessional collaboration is associated with an improvement in quality of care. Interprofessional collaboration is fundamental in the delivery of patient-centered and coordinated care. Interprofessional collaboration requires a connection with the interprofessional education. Abstract: Improvement of chronic disease management demands effective collaborative relationships between health and social-care which is achieved through teamwork. Interprofessional Education (IPE) and Interprofessional Collaboration (IPC) are recognized as essential for the delivery of effective and efficient healthcare. Although IPC and IPE are key components of primary care, evidence of studies evaluating how an IPE intervention prior to IPC improved chronic patient outcomes remains scarce. The aim of this study was to assess the impact of IPC interventions on the management of chronic patients compared to usual care. A systematic review and meta-analysis of Randomized Controlled Trials (RCTs) on IPC interventions on chronicity management and their impact on clinical and process outcomes was conducted. Of the 11, 128 papers initially retrieved, 23 met the inclusion criteria. Meta-analyses results showed the reduction of systolic blood pressure (Mean Difference (MD) -3.70; 95 % CI -7.39, -0.01), glycosylated hemoglobin (MD -0.20; 95 % CI -0.47, -0.07), LDL cholesterol (MD -5.74; 95 % CI -9.34, -2.14), diastolic blood pressure (MD -1.95; 95 % CI -3.18, -0.72), days of hospitalization (MD -2.22; 95 % CI -4.30, -0.140). A number of positive findings for outcomes related to IPC were found reflecting an improvement of quality of care and an enhancement in the delivery of patient-centered and coordinated care. Moreover, the need for a purposeful systemic approach linking interprofessional education with interprofessional collaboration and patient health and wellbeing is necessary.